EFFECT OF DRAFT LOAD ON LACTATE DEHYDROGENASE AND CREATINE KINASE ACTIVITIES IN MULES.(Equusasinus x Equuscaballus - Sareen, M; Moolchandani, A (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
This study was carried out to assess the effects of draft load on serum creatine kinase and lactated ehydorgenase activities in mule. Five adult mules of 5 to 6 years of age were subjected to loading exercise (i.e. 10% draft load for 1 to 5 days and 20% draft load from 6th to 10th day). A highly significant (P<0.01) increase in serum LDH activities in response to 10% and 20% draft load exercise was observed while significant (P<0.05) increase at 10% draft load and highly significant (P<0.01) increase at 20% draft load was observed in CK activities.